2019
DOI: 10.1002/jpen.1678
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hormone Profiles Associated With Enteral Nutrition Tolerance and Gastric Emptying in Pediatric Critical Illness: A Pilot Study

Abstract: Background Enteral nutrition (EN) intolerance and delayed gastric emptying are prevalent in pediatric critical illness and limit EN delivery. Gastrointestinal (GI) hormones may be associated with EN intolerance and delayed gastric emptying in this cohort. Methods We determined GI hormone levels, time to achieve 50% of EN goal, and gastric emptying in critically ill children. Total amylin, active ghrelin, total glucagon‐like peptide‐1 (GLP‐1), total gastric inhibitory polypeptide, glucagon, and total peptide‐YY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
12
1
1
Order By: Relevance
“…These studies have shown that levels of glucagon‐like peptide 1 (GLP‐1), PYY, and ghrelin were statistically higher in critically ill populations compared with healthy controls. This was linked with delayed gastric emptying, enteral nutrition (EN) intolerance, and poor clinical outcomes 9–12 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have shown that levels of glucagon‐like peptide 1 (GLP‐1), PYY, and ghrelin were statistically higher in critically ill populations compared with healthy controls. This was linked with delayed gastric emptying, enteral nutrition (EN) intolerance, and poor clinical outcomes 9–12 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Emerging studies recorded alterations in the levels of these gut hormones among critically ill adults. [9][10][11][12] These studies have shown that levels of glucagon-like peptide 1 (GLP-1), PYY, and ghrelin were statistically higher in critically ill populations compared with healthy controls. This was linked with delayed gastric emptying, enteral nutrition (EN) intolerance, and poor clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early enteral nutrition (EN) is recommended in critically ill children receiving invasive and non-invasive ventilation mechanical support (1). However, EN tolerance may be challenging in this setting by multifactorial gastroparesis and paralytic ileus (opioid use, bed rest, altered gut hormone secretion, plasmaelectrolyte disturbances, systemic inflammatory response syndrome) (2)(3)(4). The resulting increase in gastric volume may potentially lead to vomiting and aspiration and result in ventilation-associated pneumonia (VAP), the occurrence of which remains low in children (5,6).…”
Section: Introductionmentioning
confidence: 99%